1996
DOI: 10.1016/s1059-1311(96)80027-6
|View full text |Cite
|
Sign up to set email alerts
|

Startle disease—hyperekplexia (two sibling cases)

Abstract: Two sisters aged 12 and 13 applied to our hospital with complaints of jerking tonic contraction triggered by sudden noise. Diffuse bilaterally polyspike-wave discharges appeared on waking electroencephalography and during that time a startle-induced tonic contraction was seen. Their neurological examinations and neuro-radiological imaging were normal except for hyperreflexia. We presented these cases because of being rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Affected neonates suffer from prolonged periods of rigidity and are at risk for sudden death from apnea as in our first case study and the cases reported by Nigro et al [12]. The tonic attacks can be triggered by gentle percussion at the base of the nose, other tactile stimulation like bath, or visual stimulation [1]. Sudden loud sounds (telephone) or heat can also elicit tonic attack [5].…”
Section: Discussionmentioning
confidence: 94%
“…Affected neonates suffer from prolonged periods of rigidity and are at risk for sudden death from apnea as in our first case study and the cases reported by Nigro et al [12]. The tonic attacks can be triggered by gentle percussion at the base of the nose, other tactile stimulation like bath, or visual stimulation [1]. Sudden loud sounds (telephone) or heat can also elicit tonic attack [5].…”
Section: Discussionmentioning
confidence: 94%
“…One double-blind, placebo controlled, cross-over study that included four patients revealed that patients on clonazepam had reduced startle activity compared to vigabatrin as measured by startle to auditory stimuli. 67 Despite often dramatic response to clonazepam, 2,4,[7][8][9]16,23,25,26,29,30,[49][50][51]53,67 there are other reports that have found clonazepam to be less effective. 5,11,16,27,31,61 Saenz-Lope et al 27 found clonazepam ineffective in their three patients but had some success with the use of valproic acid and a combination of hydroxytryptophan and piracetam.…”
Section: Clonazepammentioning
confidence: 99%